Motivational factors and constraints of dairy farmers trained by Krishi Vigyan Kendra
The study was conducted in Shivamogga district of Karnataka state to analyse the motivational factors, constraints and to enlist suggestions of farmers trained on dairy management practices by KVK, Shivamogga. In all 120 trained farmers from 12 villages constituted the sample for the study. The findings revealed that the factors viz., to increase income from dairy by learning new practices (76.66%